Antibacterial Activity of Chitosan, Trisodium Citrate and Acetic Acid Against Staphylococcus Aureus Bacteria Isolated From Raw Milk In Baghdad City - Zina Saab Khudhir; Zina Saab Khudhir (مجلة الانبار للعلوم البيطرية)
Staphylococcus aureus bacteria is cause of dangerous food poisoning through contamination of raw milk; therefore, this study aimed to determine the prevalence of S. aureus in raw milk sold in local markets of Baghdad city and the antibacterial activity of chitosan, trisodium citrate and acetic acid against the pathogenic bacteria, the antibacterial susceptibility profile of isolates was performed by using (13) antibacterial agents using Kirby–Bauer disc diffusion technique. the results showed that (3) samples out of 25 samples (12%) were isolated from raw milk, all isolates were positive to the experimental tests characterized as S. aureus depending on the cultural, biochemical, serological and molecular examinations. The PCR technique used to verify the positive isolates by targeting the (nuc) gene, the molecular size (181 bp), the antibacterial activity was done by broth and agar dilution method with detection the bacterial counts. the Initial counting (mean) log CFU/ ml of isolates was 4.623 CFU/ml. The minimum inhibitory concentration of chitosan and acetic acid against Staphylococcus aureus by macro-broth dilution method was 20and 1,25 mg /ml respectively, while trisodium citrate had no inhibitory activity against the exanimated bacteria. The antibiotic susceptibility profile for positive isolates showed that all isolates were resistant to (ampicillin, methicillin, Cefixime and Cefoxitin),in conclusion comparing the effects of the three antibacterial agents against S. aureus causes contamination of cow raw milk sold in Baghdad city, 1.25 mg/ml of the acetic acid was found effective with higher antibacterial activity, followed by chitosan 2 mg /ml, while trisodium citrate showed no antibacterial effect. [AJVS 2024; 17(2.000): 80-94]